2023
DOI: 10.1002/jia2.26086
|View full text |Cite
|
Sign up to set email alerts
|

Association of demographics, HCV co‐infection, HIV‐1 subtypes and genetic clustering with late HIV diagnosis: a retrospective analysis from the Japanese Drug Resistance HIV‐1 Surveillance Network

Abstract: Introduction Late diagnosis of the human immunodeficiency virus (HIV) is a major concern epidemiologically, socially and for national healthcare systems. Although the association of certain demographics with late HIV diagnosis has been reported in several studies, the association of other factors, including clinical and phylogenetic factors, remains unclear. In the present study, we conducted a nationwide analysis to explore the association of demographics, clinical factors, HIV‐1 subtypes/circulating recombin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…No sample displayed any mixed heterologous subtypes. This subtype trend is similar to the recent epidemic report throughout Japan 16 .
Figure 2 Success and failure rates of HIV-1 pangenome amplification via RT–PCR and nested PCR for clinical samples (n = 121) with different viral loads.
…”
Section: Resultssupporting
confidence: 91%
“…No sample displayed any mixed heterologous subtypes. This subtype trend is similar to the recent epidemic report throughout Japan 16 .
Figure 2 Success and failure rates of HIV-1 pangenome amplification via RT–PCR and nested PCR for clinical samples (n = 121) with different viral loads.
…”
Section: Resultssupporting
confidence: 91%
“…Other studies performed during a similar timeframe (2017 to 2020, 2019 to 2020 and 2015 to 2020) also revealed that male and older patients are at greater risk of late HIV presentation [ 23 , 24 , 25 ]. Additionally, other LP risk factors, including bisexual transmission, heterosexual transmission, being married, SSA origin, tuberculosis or hepatitis C virus coinfection, lower socioeconomic status and the fear of stigma, have been reported in various studies [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. The discrepancies observed among those studies highlight the importance of identifying populations at risk of late presentation and developing specific guidelines according to the region.…”
Section: Discussionmentioning
confidence: 99%